PENGARUH PENGGUNAAN METODE RESITASI DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR FISIKA PADA SISWA KELAS VIII MTs NUNGGI - Erniwati Erniwati (Lensa: Jurnal Kependidikan Fisika, 2013)
Students are required to learn in solving problems in the form of tasks taken. This study aims to find the effect of recitation methods to improve physics learning outcomes and physical learning outcomes in grade VIII students MTs Nunggi. The method used is experimental research. The results showed that the students' activity in the experimental class was very active (average score 3.67) and the control class was quite active (average score 2.33). Teacher activity in the experimental class has been very active (average score 3.67) and in the control class is quite active (average score 2.16). Student learning result data that in experiment and control class is processed using t-test equation. The t-test value is 2.79 at the 5% significance level of 2.79 and the t-table (t-test> t-table). Therefore the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. We conclude that the method of recitation for improving physics learning outcomes in grade VII MTS Nunggi has an effect of 13.63%.